Legal Protection for Child Offenders in Bullying Cases: Challenges and Deviations in Restorative Justice Practice - Ahmad Arifulloh; Andri Winjaya Laksana; Moh Aris Siswanto; Toni Triyanto (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
This study examines legal protection for children as perpetrators of bullying through the application of restorative justice. The purpose of the research is to analyze how restorative justice is implemented in resolving bullying crimes committed by minors, identify the obstacles encountered in practice, and formulate relevant solutions. This research is normative legal research using a statutory approach. Data were collected through literature studies, including legislation, academic literature, and previous research findings, and then analyzed qualitatively. The results indicate that applying restorative justice to children who commit bullying can be carried out through the diversion mechanism, namely, the transfer of juvenile case settlement from the formal criminal justice process to non-litigation mechanisms outside the court system. This mechanism is in accordance with Law Number 11 of 2012 on the Juvenile Criminal Justice System, which prioritizes the best interests of the child. From the perspective of criminal law theory, the implementation of restorative justice represents a positive deviation from the retributive justice concept, which is oriented toward punishment and retribution. Restorative justice shifts the focus of criminal justice from punishing offenders toward restoring losses experienced by victims, repairing social harm caused by the crime, and reintegrating relationships between victims, offenders, their families, and the community. The academic contribution of this study lies in strengthening the discourse on restorative justice in bullying cases involving minors by providing normative arguments that the restorative approach aligns more closely with humanitarian principles, children's rights, and the best interests of the child than conventional retributive approaches. These findings offer theoretical and practical insights for policymakers, law enforcement officers, educators, and child protection institutions to optimize diversion mechanisms to address bullying that emphasizes punishment rather than social recovery and build awareness, empathy, and social recovery for all parties involved